2019
DOI: 10.1007/s00027-019-0653-0
|View full text |Cite|
|
Sign up to set email alerts
|

Photo-reactivity of dissolved organic carbon in the freshwater continuum

Abstract: The patterns in dissolved organic carbon (DOC) photo-mineralization along the freshwater continuum from land to sea are poorly known. Specifically, it has not been resolved how the photo-degradation of DOC into CO 2 (PD) depends on the combination of intrinsic properties of DOC and extrinsic variables that affect the photo-reactions. We measured PD per unit of absorbed ultraviolet light energy (PD-E w ) in headwater streams, lakes, intermediate rivers and river mouths in Sweden. Surprisingly, no trend of decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…For example, anaerobic C mineralization of thermokarst lake sediments is fairly well established in discontinuous permafrost zone of peat bogs in western Siberia (Audry et al, 2011) and Canada (Deshpande et al, 2017). Second, the photo-degradation (Panneer Selvam et al, 2019) of OM as well as the photo-stimulation of the microbial respiration, which is known to decrease along the HC (Cory and Kling, 2018), could enhance natural CO2 emission compared to laboratory incubations. Third, the POC present in the water column in the field can sizably contribute to overall CO2 emissions from surface waters: it has been shown that, during laboratory incubations of boreal and subarctic waters, the POC is 15 times more reactive towards biodegradation than DOC (Attermeyer et al, 2018).…”
Section: How Does Co2 Production From Experimental Doc Biodegradation Relate To Fieldbased Fluxes Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, anaerobic C mineralization of thermokarst lake sediments is fairly well established in discontinuous permafrost zone of peat bogs in western Siberia (Audry et al, 2011) and Canada (Deshpande et al, 2017). Second, the photo-degradation (Panneer Selvam et al, 2019) of OM as well as the photo-stimulation of the microbial respiration, which is known to decrease along the HC (Cory and Kling, 2018), could enhance natural CO2 emission compared to laboratory incubations. Third, the POC present in the water column in the field can sizably contribute to overall CO2 emissions from surface waters: it has been shown that, during laboratory incubations of boreal and subarctic waters, the POC is 15 times more reactive towards biodegradation than DOC (Attermeyer et al, 2018).…”
Section: How Does Co2 Production From Experimental Doc Biodegradation Relate To Fieldbased Fluxes Estimatesmentioning
confidence: 99%
“…In Arctic regions, the hydrological continuum (HC) is highly dependent on the maturation cycle of water bodies. All steps of HC are especially important as they can influence the biochemical properties, photo-(Panneer Selvam et al, 2019) and bio-degradability (Liu et al, 2019;Vonk et al, 2015) of dissolved organic matter (DOM). Since the transport of thawed permafrost organic C can spatially relocate the emissions of greenhouses gases (Vonk and Gustafsson, 2013), the heterogeneity of waterbodies observed along a hydrological continuum is a key point to understand the C cycle in these regions.…”
Section: Introductionmentioning
confidence: 99%
“…As SUVA 400 is a measure of the aromatic character of the DOC, this implies that aromaticity is increasing at decreasing pH. In acidic waters, DIC photoproduction rates have frequently been reported to increase with decreasing pH (Panneer Selvam et al 2019). In alkaline waters, the relationship between photochemical degradation of DOC and pH is less certain.…”
Section: Discussionmentioning
confidence: 99%
“…This photochemical reactivity or apparent quantum yield (AQY) of DIC photoproduction is defined as moles photochemically produced DIC per mole photons absorbed by the DOC pool (Miller et al 2002). Besides the quantity of DOC, studies have found photochemical DIC production rates to be dependent on its quality, as well as on water chemistry, such as pH and iron concentration (Lindell et al 1995; Bertilsson and Tranvik 2000; Panneer Selvam et al 2019) while other studies have found no such relationships (Cory et al 2014). A significant share of the AQY variability between lakes can be explained by simple optical parameters (Koehler et al 2016), allowing for estimates of photochemical DIC production when system‐specific AQY spectra are not available.…”
mentioning
confidence: 99%
“…Rivers do not only transport but also transform organic matter on its way downstream towards the ocean via photochemical and microbial processes in the water column. [8][9][10] Photo-chemical reactions, which are strongly site dependent, 11 can preferentially degrade aromatic compounds deriving from pyrogenic sources. 12 In-stream microbiota, especially biofilm communities which are hotspots of microbial functioning, are central to the role of fluvial ecosystems as bioreactors of terrestrial material.…”
Section: Introductionmentioning
confidence: 99%